Effects of Low Level Laser Therapy on Knee Pain and Functional Status among Patients with Knee Osteoarthritis - Abeel Ashraf, Saima Riaz, Hafiz Muhammad Arslan, Rehan Ramzan Khan, Rashid Naeem, Ammara Malik (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To determine the outcomes of low level laser therapy on knee pain and functional status among patients with knee osteoarthritis. Methodology: A randomized controlled trial was conducted in physiotherapy department of Allied Hospital Faisalabad. Thirty four patients were randomly divided into experimental group treated with low level laser therapy combined with conventional exercises and control group treated with conventional exercises only. Numeric Pain Rating Scale, Western Ontario McMaster Universities Osteoarthritis Index (WOMAC) and goniometer were used as data collection tools. All the patients received 9 treatment sessions, 3 sessions per week for 3 weeks. Results: Outcome measures including numeric pain rating scale, Western Ontario McMaster Universities Osteoarthritis Index (WOMAC) and goniometer showed significant results (p<0.05) after treatment in both groups but comparing pre and post mean difference of all these outcome measures depicted better results in experimental group treated with low level laser therapy combined with conventional exercises. Conclusion: This study concluded that low level laser therapy had significant effects on pain, range of motion and functional status in patients with knee osteoarthritis.